Trypanosoma vivax infection dynamics in a cattle herd maintained in a transition area between Pantanal lowlands and highlands of Mato Grosso do Sul, Brazil - Martins, Charles F.; Madruga, Claudio R.; Koller, Wilson W.; Araujo, Flabio R.; Soares, Cleber O.; Kessler, Raul H.; Melo, Elaine S. P.; Rios, Laura R.; Almeida, Robson C. F.; Lima, Manoel S. C.; Barros, Antonio Thadeu M.; Marques, Luiz C. [UNESP] (Revista Pesquisa Veterinaria Brasileira, 2008)
Trypanosoma vivax outbreaks in beef cattle in the Pantanal region of Mato Grosso do Sul state, Brazil, causes relevant economical impact due to weight loss, abortion and mortality. Cattle moved from the Pantanal to adjacent areas of this ecosystem for breeding and fattening is a common feature. Therefore an epidemiological study on breeding cows in the transition area between Pantanal lowland and adjacent highlands of Mato Grosso do Sul was performed to determine the T. vivax infection dynamics and outbreak risk. Three experimental groups were formed: Group 1 consisted of cows parasitologically negative by the Woo test and in the enzyme-linked immunosorbent assay for T. vivax antibody detection (Tv-ELISA-Ab); Group 2 parasitologically negative and positive in the Tv-ELISA-Ab; and in Group 3 cows were parasitologically positive and with positive reactions in the Tv-ELISA-Ab. During 24 months, the cows' dislodgment between the above established groups was monitored by Woo test and Tv-ELISA-Ab exams. The tabanid population was also monitored and the highest number occurred during the rainy season. Although parasitemias were detected only in the first four samplings of the experimental period, the cows could be considered as trypanotolerant, because no clinical signs were observed. Despite the higher T. vivax incidence during the dry season, no disease symptoms were seen. Even though T. vivax epidemiological situation in the herd was characterized as endemic with seasonal variation, the probability of outbreaks was null within the conditions of the study.
Keywords: Trypanosoma (Dutonella) vivax; cattle; tabanids; infection dynamics; epidemiology